The customer's satisfaction evaluation of Portuguese mould makers based on the ECSI approach - Irene Ferreira (2008)
In recent years, the European CustomerSatisfaction Index (ECSI) model has become apopular way of assessing customer satisfaction.Customer satisfaction and retention areconsidered as key issues for organizations intodays competitive market place, turning it into avital concern to achieve customer loyalty.Therefore, it was necessary to develop onereliable and independent frame-of-reference ofcustomer satisfaction, allowing the comparisonbetween companies within the same sector and/orthat operate in the same country, or at amacroeconomic level. The ECSI model is aframework, adapted from the Swedish CustomerSatisfaction Barometer and American CustomerSatisfaction Index, which aims to harmonize theCustomer Satisfaction Indexes (CSI) in Europe.This paper describes one approach based on theECSI model, developed to assess the satisfactionof Portuguese injection mould customers. Twomain groups of customers were studied, thePortuguese and the American injection companies,where the data was collected by a self-respondentquestionnaire sent by e-mail. The ECSI modelswere estimated according to two main techniques,the covariance-based or hard modelling methods(sometimes called LISREL) and the componentbasedtechniques or soft modelling methods (e.g.Partial Least Squares). Therefore, it was possibleto compare the satisfaction of the Portuguese andAmerican customers, as well as comparing theperformance of the two main techniques used toestimate the models.